TourismShare - Nuno Areias (2017)
TourismShare is a context-aware recommendation platform that allows tourists to share private locations and videos and obtain recommendations regarding potential Points of Interest (POI), including complementary articles and videos. The user experience is enhanced with the addition audio immersion during video playback and automatic recommendation features. The developed system consists of a distributed application comprising a front-end client module (Android application), which provides the user interface and consumes directly external support services, and the back-end server module, which includes the central database and recommendation service. The communication between the client and server modules is implemented by a dedicated application level protocol. The recommendations, which are based on the user context (user position, date and current time, past ratings and user activity level), are provide on request or automatically, whenever POI of great relevance to the user are found. The recommended POI are presented on a map, showing the timetable together with complementary articles and videos. The audio immersion at video playback time takes into account the weather conditions of the video recording and the user activity level.